Medical resource utilization and costs associated with autosomal dominant polycystic kidney disease in the USA: a retrospective matched cohort analysis of private insurer data - Knight T; Schaefer C; Krasa H; Oberdhan D; Chapman A; Perrone RD (Dove Medical Press, 2015)
Tyler Knight,1 Caroline Schaefer,1 Holly Krasa,2 Dorothee Oberdhan,2 Arlene Chapman,3 Ronald D Perrone4 1Covance Market Access Services Inc., Gaithersburg, MD, 2Otsuka Pharmaceutical Development and Commercialization, Inc., Rockville, MD, 3Emory University, Atlanta, GA, 4Tufts Medical Center and Tufts University School of Medicine, Boston, MA, USA Background: Autosomal dominant polycystic kidney disease (ADPKD) results in kidney cyst development and enlargement, resulting in chronic kidney disease (CKD) leading to renal failure. This study sought to determine if ADPKD patients in the early stages of CKD contribute to a sizable economic burden for the US health care system. Methods: This was a retrospective, matched cohort study, reviewing medical resource utilization (MRU) and costs for adults in a US private-payer claims database with a diagnosis code of ADPKD (ICD-9-CM 753.13). ADPKD patients were matched by age grouping (0–17, 18–34, 35–44, 45–54, 55–64, and 65+ years) and sex to controls to understand the burden of ADPKD. Descriptive statistics on 6-month MRU and costs were assessed by CKD stages, dialysis use, or previous renal transplant. Results: The analysis included ADPKD patients in CKD stages 1–5 (n=316 to n=860), dialysis (n=586), and post-transplant (n=615). Mean ages did not differ across CKD stages (range 43–56 years). Men were the majority in the later stages but the minority in the early stages. The proportion of patients with at least one hospitalization increased with CKD stage, (12% to >40% CKD stage 2 to stage 5, dialysis or post-transplant). The majority had at least one hospital outpatient visit and at least one pharmacy claim. Total 6-month per-patient costs were greater among ADPKD patients than in age-matched and sex-matched healthy non-ADPKD controls (P<0.001 for all comparisons). Conclusion: ADPKD patients with normal kidney function are associated with a significant economic burden to the health care system relative to the general population. Any treatments that delay progression to later stages of CKD may provide potential health care cost offsets. Keywords: autosomal dominant polycystic kidney disease, medical resource utilization, chronic kidney disease